Fabrication and Photocatalytic Properties of ZnSe Nanorod Films. (28th June 2016) - Yin, Jiajia; Yang, Chao; Yang, Xianheng; Wang, Shutong; Zhang, Hua; Zhou, Shouhuan; Feng, Guoying
Abstract : ZnSe nanorod films grown on fused quartz glass substrates via a simple two-step synthesis protocol were demonstrated to be environmentally safe and effective recyclable photocatalysts. These films showed greatly enhanced photocatalytic activity compared to pulsed laser deposition ZnSe films in the degradation of methyl orange dye solutions. The well-crystalized ZnSe nanorods had a length of 15 µ m and a diameter of 200 nm and were densely grown on the substrate. The morphology, crystal structure, crystal phase, and photophysical properties of the ZnSe nanorod films were investigated using field-emission scanning electron microscopy (FE-SEM), UV-Vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and high resolution transmission electron microscopy (HRTEM).